Статистичні характеристики лексики основних функціональних стилів української мови: спроба порівняння - Бук, С. (Лексикографічний бюлетень, 2006)
Résumé: In the article, for the first time, the main statistical characteristics, such as the variety, exclusiveness, concentration indices are compared for the vocabulary of six modern Ukrainian language functional styles: belles-lettres, poetry, journalistic, colloquial, scientific and official. The research has been done at the material of the 6 appropriate frequency dictionaries and the number of words and wordforms is given as well. The result is the complete correlation of all mentioned statistical characteristics.